Addis Ababa City : Public Expenditure Review - World Bank (Washington, DC, 2013)
This study on Addis Ababa is part of the national Public Expenditure Review (PFR-2010) study and the report is one of the four regional PER-2010 reports. The objective of the study is to review the institutional arrangements for managing public finances in Addis Ababa city administration, to assess the level, trend, and composition of public revenue, spending and financing as well as to review the planning and budgeting process. The study has also tried to evaluate the city administration's service delivery outcomes in education and health sectors as well as road and housing development which are the two most prioritized sectors in terms of their share from the total capital outlay. The report has reviewed different studies, plans and performance reports of the various sectors in the city administration. The analysis is largely based on information and data obtained from different bureaus of the city administration especially Addis Ababa bureau of finance and economic development.